(untitled) (Comprehensive Journal of Science, 2026)
The study aimed to explore the impact of digital transformation on the job performance of employees in the Graduate Studies Administration at the University of Zawiya. A descriptive‑analytical approach was used, employing a five‑point Likert scale questionnaire administered to all administration staff (N = 53). Data were analyzed using SPSS version 26. Cronbach’s alpha indicated good reliability (α = 0.665–0.870). All dimension means exceeded the neutral value of 3 and were statistically significant (p < 0.05). Results showed enhanced operational efficiency, reduced administrative errors, and higher employee satisfaction. Major challenges included insufficient technical resources and resistance to organizational change. The study recommends strengthening digital infrastructure, providing ongoing training programs, and adopting a comprehensive change‑management strategy to sustain the benefits of digital transformation.